2017
DOI: 10.1115/1.4035751
|View full text |Cite
|
Sign up to set email alerts
|

Practical Data Mining and Artificial Neural Network Modeling for Steam-Assisted Gravity Drainage Production Analysis

Abstract: Production forecast of steam-assisted gravity drainage (SAGD) in heterogeneous reservoir is important for reservoir management and optimization of development strategies for oil sand operations. In this work, artificial intelligence (AI) approaches are employed as a complementary tool for production forecast and pattern recognition of highly nonlinear relationships between system variables. Field data from more than 2000 wells are extracted from various publicly available sources. It consists of petrophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…K-fold cross-validation is used to assess the performance of the model on unseen data and detect overfitting . Additionally, the permutation variable importance (PVI) approach is used to evaluate the relative importance of all variables in the models developed by ANN and MLR …”
Section: Methodsmentioning
confidence: 99%
“…K-fold cross-validation is used to assess the performance of the model on unseen data and detect overfitting . Additionally, the permutation variable importance (PVI) approach is used to evaluate the relative importance of all variables in the models developed by ANN and MLR …”
Section: Methodsmentioning
confidence: 99%
“…It can be concluded that the increase of fracture permeability can improve oil production, whereas the existence of horizontal fractures would reduce oil production (Hosseini et al, 2017). Ma et al, (2017) used artificial intelligence approaches to predict and improve performance of the SAGD processes. By co-injecting solvents into the steam stream during SAGD processes, a significant increment of oil production has been observed (Bera and Babadagli, 2015).…”
Section: Thermal-based Methodsmentioning
confidence: 99%
“…Today, ANNs find applications in a wide array of scientific and technological domains, especially within the industrial sector. They serve as pivotal tools for diverse applications such as process monitoring and control [109], power systems [110], medical diagnosis [111], stock market prediction [112], nuclear plant control [113], robotics [114], communication systems [115], data mining [116], pattern recognition [117], and decision fusion [118].…”
Section: Machine Learningmentioning
confidence: 99%